APC gene mutations and extraintestinal phenotype of familial adenomatous polyposis. - Giardiello, F M (1997)
BACKGROUND: Familial adenomatous polyposis (FAP) is caused by germline mutation of the adenomatous polyposis coli (APC) gene on chromosome 5q. AIMS: This study assessed genotype-phenotype correlations for extraintestinal lesions in FAP. METHODS: Mutations of the APC gene were compared with the occurrence of seven extraintestinal manifestations in 475 FAP patients from 51 families. The frequency of manifestations was adjusted for different ages of patients using person years of exposure. In pedigrees without identified APC gene mutation, analysis of linkage to chromosome 5q and/or assessment of neoplasms for replication errors characteristic of mutation in mismatch repair genes were performed. RESULTS: FAP patients from the 42 families (82%) with identified mutations of the APC gene had more frequent expression of extraintestinal manifestations than affected individuals without identified mutations (risk ratio 1.2-4.0; significant difference for cutaneous cysts). The presence of a cutaneous cyst or extraintestinal cancer significantly increased the likelihood of detection of a mutation in the APC gene (94% and 92% respectively; p < 0.05). In patients without identified APC gene mutation, linkage to the APC gene was found in one large family (lod = 5.1, theta 0.01), and replication error phenotype was absent in all 24 neoplasms from 16 members of these nine pedigrees. Expression of pigmented ocular fundus lesions was strongly associated with mutations in codons 541-1309, but no other extraintestinal manifestations were related to mutation position. Multiplicity of extraintestinal manifestations was high with mutation in codons 1465, 1546, and 2621. CONCLUSIONS: Patients with the colorectal phenotype of FAP but no extraintestinal manifestations may have non-truncating mutations of the APC gene or mutation in a gene other than APC or mismatch repair genes. The site of APC gene mutation is associated with pigmented ocular fundus lesions (codons 542-1309) and predisposition to multiplicity of extraintestinal manifestations (codons 1465, 1546, and 2621).